A Hydrogen‐Bond Flip‐Flop through a Bjerrum‐Type Defect1. Issue 9 (18th February 2013) - Olschewski, Martin; Lindner, Jörg; Vöhringer, Peter
<x xml:space="preserve">Abstract</x> Back and forth: Femtosecond two‐dimensional infrared exchange spectroscopy was used to study the dynamics of the reversal of an intramolecular hydrogen bond. The H‐bond reversal resembles a flip‐flop motion that is facilitated by two concerted disrotatory torsional isomerizations and that occurs on a time scale of about 2 ps.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>